When the Son of the Indonesia President Becomes a Party Chairman: An Analysis of Political Capital and Public Response - Subekti, Dimas; Putra, Dinda Syufradian; Pasaribu, Ian (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2024)
This research is motivated by the case of President Joko Widodo's son, Kaesang Pangareb, who became chairman of the Indonesian Solidarity Party (PSI) after becoming a cadre for two days. Therefore, this study aims to explain the political capital of Kaesang Pangareb in becoming the chairman of PSI and how the public responds to the process. This research uses a qualitative method with a case study approach. The findings of this study explain that there are three critical political capitals owned by Kaesang Pangareb, the president's son, who became the party chairman in a short time. First, the representation of young people who perform well in building businesses. Then, there was solid political support from his father, the active president of Indonesia. This support from President Joko Widodo has enormous power as a form of privilege for Kaesang Pangareb to be elected as chairman in such a quick process. Moreover, the support from the PSI party elite also significantly contributes to consolidating cadres at the central and regional levels to support Kaesang Pangareb in becoming chairman. Then, the public response, both in the real world and in cyberspace related to this case, shows a positive perception and supports Kaesang Pangareb's political movement.